Temporary tracheotomy in microvascular reconstruction in maxillofacial surgery: Benefit or threat?. Issue 4 (April 2019) - Goetz, Carolin; Burian, Nora-Maria; Weitz, Jochen; Wolff, Klaus-Dietrich; Bissinger, Oliver
Abstract: Background: Temporary tracheotomies are often used in oral microvascular flap reconstruction surgery to secure postoperative airway management and avoid emergency tracheotomies. Even when planned electively, a tracheotomy can cause severe and life-threatening complications. The aim of this study was to evaluate the complications of tracheotomies performed on oral cancer patients with microvascular flap reconstructions and differentiated patterns, which could lead to postoperative complications. Methods: 150 patients, treated in the Department of Oral and Maxillofacial Surgery from March 2017 to August 2018, were included in this study. Patient records and perioperative data were analysed and the following specific items were evaluated: time after surgery until removal of the tracheal cannula, complications, cause and point of time of reinsertion of the cannula, anticoagulative treatment, ASA grade (American Society of Anaesthesiologists), TNM stage, and patient-specific data. Results: 30 patients (20%) developed tracheotomy-associated complications, most commonly pneumonia (50%). There was a significant correlation between the time period until removal of the cannula and the occurrence of complications such as pneumonia and bleeding. Conclusion: The results of our study lead us to recommend continuing to perform temporary tracheotomies in oral cancer surgery with microvascular flap reconstruction. The overall complication rate is low and postoperative airway management can be performed in a safe and controlled manner. Nevertheless, the time period for the inserted cannula should be kept as short as possible.